The BETA Project. - Jensen, Peter; Nygaard, Kristen (DAIMI Report Series, 1976)
The BETA system programming language is being developed as a part of the Joint Language Project going on in Aarhus, Denmark and Oslo, Norway. The report proposes that the Norwegian Computing Center should start an associated project aimed at an implementation of the BETA language, to make it available as a tool in developing programs for computers based upon micro-computer technology. Never published This publication is not available as a full text PDF.